Particulate and Dissolved Black Carbon in Bohai and Laizhou Bays, China: Distributions, Sources, and Contrasts Under Two Distinct Fluvial Hydrological Regimes - Fang, Yin; Huang, Guopei; Chen, Yingjun; Hu, Limin; Lin, Jun; Lin, Tian (Frontiers in Earth Science, 2021)
Coastal seas, including coastal bays, are the geographically critical transitional zone that links terrestrial and open oceanic ecosystems. Organic carbon cycling in this area is a dynamic and disproportionally key component in the global carbon cycle and budget. As the thermally-transformed organic carbon produced exclusively from the incomplete combustion of biomass and fossil fuels, the recalcitrance and resultant longer environmental residence times result in important implications of black carbon (BC) in the global carbon budget. However, the environmental dynamics of BC in coastal seas have not well been constrained. In this study, we conducted one seawater sampling campaign in the high-intensity BC emission influenced Bohai Bay (BHB) and Laizhou Bay (LZB) in 2013, and quantified both particulate and dissolved BC (PBC and DBC). We elaborated the distributions, sources, and associated influencing factors of PBC and DBC in BHB and LZB in 2013, and simultaneously contrasted the PBC and DBC quantity and quality under two distinct fluvial hydrological regimes of 2013 and 2014 (discussed in Fang et al. (2021)). Except for the overwhelmingly high PBC in northern BHB caused by anthropogenic point-source emission, horizontally, both PBC and DBC showed a seaward decreasing trend, suggesting that riverine discharge was the major source for PBC and DBC. Vertically, in contrast to the uniform concentrations of DBC between surface and bottom waters, the PBC levels in bottom waters was significantly higher than that in surface waters, which was primarily resulted from the intense sediment re-suspension process during this sampling period. The nearly simultaneous investigations in 2013 and 2014 revealed consistent spatial patterns of PBC and DBC quantity and quality. But significantly lower PBC and DBC quantity and quality were found in 2014 than in 2013, which were largely due to the significantly different climatic conditions (including the watershed hydrology and sunlit radiation) between these two years.